IMPORTANCE OF WORD OF MOUTH MARKETING IN MARKETING TOOLS AND AN APPLICATION TO SHAPE PURCHASING BEHAVIORS (Third Sector Social Economic Review, 2018)
business function, marketing is an activity in the center of life (whether or not these people are aware) for all people. We people want to have a positive, strong influence on other people with our costumes and the style we create. Businesses also want to have a strong impact on consumers with marketing methods and they carry out various marketing activities for this. However, there is a marketing method outside the control of the enterprise. This method is Word of Mouth marketing. With Word of Mouth Marketing, people tell other people about a product or brand in an informal environment (tea conversations, women's golden days, when they meet the road each other etc.) and they can influence other people in relation to that product or brand. Consumers can also make a judgment on the use of that product or brand in such a case. This research was conducted to measure the impact level of Word of Mouth Marketing compared with other marketing tools and to show an example application about how consumers influence purchasing behavior and how they can shape their thoughts. When the results of the research are examined, it is seen that the consumers are quite affected by the word of Mouth Marketing actions. Therefore, it is necessary for businesses to establish a customer group that will talk positively about the their products and brands.
Keywords: Word of mouth marketing; marketing; marketing communication; brand; consumer behavior